2011
DOI: 10.1016/j.expneurol.2010.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Glatiramer acetate for treatment of MS: Regulatory B cells join the cast of players

Abstract: Glatiramer acetate (GA, copolymer-1, Copaxone®) is a Food and Drug Administration-approved drug for the treatment of relapsing-remitting multiple sclerosis (MS). However, its mechanism of action remains ill-defined. The available evidence indicates that GA induces antigen-presenting cells with anti-inflammatory properties and promotes the generation of immunoregulatory T cells that suppress pathogenic T cells. A new study by Kala et al. (Exp. Neurol. 2010. 221, 136–145) now shows that B lymphocytes, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…In light of depletion therapy success, more focus is now being given to B-cells and their role in MS. The literature supports both a pathogenic (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82) and regulatory (76,(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94) role for B-cells in MS/EAE, and it is intriguing to speculate about the potential immune cell interplay between CD4 + T-cells, B-cells, and CD8 + T-cells therein. There is evidence in the literature to support a B-cell effect on CD8 + T-cells (54,55,82,(95)(96)(97)(98)(99)(100).…”
Section: Potential Cd8 + T-cell: B-cell Interactions In Ms/eae?mentioning
confidence: 94%
“…In light of depletion therapy success, more focus is now being given to B-cells and their role in MS. The literature supports both a pathogenic (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82) and regulatory (76,(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94) role for B-cells in MS/EAE, and it is intriguing to speculate about the potential immune cell interplay between CD4 + T-cells, B-cells, and CD8 + T-cells therein. There is evidence in the literature to support a B-cell effect on CD8 + T-cells (54,55,82,(95)(96)(97)(98)(99)(100).…”
Section: Potential Cd8 + T-cell: B-cell Interactions In Ms/eae?mentioning
confidence: 94%
“…Independent of the idea that Bregs constitute a true cell lineage or merely a state of activation by B cells, the production of IL-10 by a subset of B cells has proven critical for the resolution of EAE and other autoimmune disorders both in mice and humans (6, 10, 11, 21, 69). Bregs also have a role in the mechanism of action by Copaxone ® , a glatiramer acetate copolymer, approved for the treatment of relapsing-remitting MS (5, 12, 25, 52, 56). In a recent clinical trial, Ireland et al showed that treatment of relapsing-remitting MS patients with glatiramer acetate restored IL-10 production while reducing lymphotoxin-α production by peripheral B cells, thus contributing to the therapeutic effects of glatiramer acetate (53).…”
Section: Discussionmentioning
confidence: 99%
“…84,85 Bregs have also been implicated in the beneficial effects of glatiramer acetate against EAE. 86,87 In addition to IL-10, other mechanisms have been proposed for the suppressive functions of Bregs in EAE 88,89 and these include the induction of IL-10-producing Tregs 90 and the production of TGF-β, IL-35, programmed death 1 ligand 1 or Fas ligand. 88,89 Although most studies have implicated adaptive Bregs in these activities, they were unable to exclude a potential contribution of innate-like Bregs.…”
Section: Adaptive Lymphocytesmentioning
confidence: 99%